Experimental Study of a Gas Engine-driven Heat Pump System for Space Heating and Cooling - Zhang, Wei; Yang, Xianzhao; Wang, Tao; Peng, Xueyuan; Wang, Xiaolin (Civil Engineering Journal, 2019)
In this paper, the performance of a gas engine-driven heat pump (GEHP) was experimentally studied for space heating and cooling. An experimental test facility was developed for this purpose. The effect of key parameters on system performance was investigated under both cooling and heating modes. The results showed that as the engine speed increased from 1400 to 2000 rpm, the cooling and heating capacities increased by 23% and 28.5%, respectively while the GEHP system Primary Energy Ratio (PER) decreased by 13.5% and 11.7% in the cooling and heating modes, respectively. The system PER in the cooling mode was found lower than that in the heating mode. This indicated that heat recovery from the engine cylinder and exhaust gas was very important for improving the GEHP system performance. In the heating mode, the ambient temperature and condenser water flow rate had a large effect on the system heating capacity and PER, and insignificant effect on the gas energy input. In the cooling mode, the chilled water inlet temperature showed a large effect on both cooling capacity and gas energy input while the chilled water flow rate had a large effect on cooling capacity and insignificant effect on the gas energy input.